P-170 Proteomic Analysis of Redox-Dependent Intestinal Protein Thiol Modification by Isotope Coded Affinity-Tagged Labeling. (March 2016) - Matthews, Jason; Reedy, April; Darby, Trevor; Jones, Rheinallt; Neish, Andrew
Abstract : Background: Reactive Oxygen Species (ROS) are a family of small molecules generated during or in response to a variety of biological processes, especially tissue repair and microbial contact. Intestinal homeostasis and wound healing are regulated in part by ROS generation from epithelial-microbe interactions, as shown by previous studies from our group. ROS generation induced by microbial contact in the gut can be transduced into altered protein function by reduction/oxidation (red-ox) of key regulatory thiols on cysteine residues in cellular proteins. ROS modifications of protein thiols can change protein conformation and activity by altering disulfide bonds, or degree of protein oxidation, leading to changes in downstream signaling events and cellular functions. Methods: Recent advances in cysteine labeling with isotope coded affinity tags (ICATs) allows for the mass spectrophotometric identification of thiol modifications by differentially labeling individual cysteine residues, that are either reduced or oxidized, with distinct ICATs to determine residue-specific red-ox changes in response to a variety of cellular stimuli. The goal of our studies is to determine ROS-dependent proteomic changes in gut intestinal epithelial cells during wound repair in response to signaling generated by gut-microbial interactions in order to further elucidate probiotic signaling mechanisms that enhance intestinal homeostasis. Results: We have begun our investigation by analyzing the thiol modification in the proteome of human intestinal epithelial cells by either peroxide treatment, or by scratch-wounding of intestinal epithelial cell monolayers and found statistically significant changes in pathways involving RNA transcription, transport and translation, as well as proteins involved in protein degradation, stress response, and cytoskeletal/junctional dynamics. Conclusions: Here we demonstrate the powerful use of the ICAT technology in analyzing proteomic changes at the cysteine level within intestinal epithelial cells. Ongoing efforts by our group will continue to elucidate proteomic targets and biological functions associated with a diversity of ROS signals necessary for gut homeostasis and wound healing.